Free deep inferior epigastric artery perforator flap techniques for the immediate post modified radial mastectomy reconstruction - Zheng, Min; Lin, Hai-duo; Jiang, Zheng-cai; Yang, Jing-quan (Zhong hua yi xue za zhi, 2008)
To discuss the feasibility and method of immediate breast reconstruction right after modified radical mastectomy in early breast carcinoma patients. Deep inferior epigastric artery perforation flaps were immediately applied on patients to reconstruct the breast after the skin-sparing mastectomy. The breasts were shaped after the deep inferior epigastric artery and vein were anastomosed to the thoracodorsal artery and vein. In 10 cases of breast reconstruction by DIEP flaps since 2005, there were completely survival in 8 flaps, distal skin necrosis in 1 flap, adiponecrosis in 1 flap. With the follow-up of 9-28 months, the reconstructed breasts were well-shaped and there were no abdominal complication in dnor sites. Ninety percent patients were satisfied with the results from the good to the best level. Most patients were satisfied with the results of mastectomy reconstruction.